A novel mutation in NF1 is associated with diverse intra-familial phenotypic variation and astrocytoma in a Chinese family. (September 2016) - Banerjee, Santasree; Dai, Yi; Liang, Shengran; Chen, Huishuang; Wang, Yanyan; Tang, Lihui; Wu, Jing; Huang, Hui
Highlights: We have studied a three generation Chinese family suffering from neurofibromatosis type 1 (NF1). We performed target exome capture based next-generation sequencing to identify the causative mutation. The mutation is a deletion mutation which is novel and causes frameshift to the NF1 protein. We performed Sanger sequencing to validate the results of the next-generation sequencing. This is the first case of a Chinese NF1 patient with intrafamilial variation in phenotype. Abstract: Neurofibromatosis type 1 (NF1) is a dysregulated neurocutaneous disorder, characterized by neurofibromas and café-au-lait spots. NF1 is caused by mutations in the NF1 gene, encoding neurofibromin. Here, we present a clinical molecular study of a three-generation Chinese family with NF1. The proband was a male patient who showed café-au-lait spots and multiple subcutaneous neurofibromas over the whole body, but his siblings only had regional lesions. The man's daughter presented with severe headache and vomiting. Neurological examination revealed an intracranial space occupying lesion. Surgery was undertaken and the histopathological examination showed a grade I-II astrocytoma. Next-Generation sequencing (Illumina HiSeq2500 Analyzers; Illumina, San Diego, CA, USA) and Sanger sequencing (ABI PRISM 3730 automated sequencer; Applied Biosystems, Foster City, CA, USA) identified the c.227delA mutation in the NF1 gene in the man. The mutation is co-segregated with the disease phenotypes among the affected members of this family and was absent in 100 healthy controls. This novel mutation results in a frameshift (p.Asn78IlefsX7) as well as truncation of neurofibromin by formation of a premature stop codon. Our results not only extended the mutational and phenotypic spectra of the gene and the disease, but also highlight the importance of the other genetic or environmental factors in the development and severity of the disease.